Long-term Clinical Outcomes of Autologous Non-activated Platelet-rich Plasma (A-PRP) Delivered Through Mechanical and Controlled Infiltration in Male and Female Androgenetic Alopecia: A 10-year Prospective Randomized Evaluator-blinded Study - Pietro Gentile (Aesthetic Surgery Journal, 2026)
Abstract Background Androgenetic alopecia (AGA) is the most common cause of progressive hair loss in men and women and is associated with significant psychosocial distress. Platelet-rich plasma (PRP) is a regenerative therapy that stimulates follicular activity, angiogenesis, and dermal papilla activation through growth factor release. Objectives This prospective randomized evaluator-blinded clinical trial evaluated the long-term efficacy and safety of autologous non-activated PRP (A-PRP) delivered through a standardized mechanical and controlled infiltration protocol. Methods Between January 2015 and January 2025, 234 patients with AGA were enrolled, including 135 men (Norwood–Hamilton I–IV) and 99 women (Ludwig I–II); 25 patients had previous confirmed COVID-19 infection. Patients received three A-PRP sessions at 30-day intervals with intradermal administration of 0.2 mL/cm2. Hair density (HD), hair thickness (HT), and total hair count (HC) were assessed by computerized trichoscopy and phototrichogram analysis at baseline, 12, 36, 60, and 120 months. Results At 12 months, HD increased by 31.4%, HT by 26.8%, and HC by 29.7% compared with baseline (p < 0.001). HD remained above baseline at 36 months (+24.1%) and 60 months (+17.3%). At 120 months, patients receiving maintenance treatment showed an 11.2% improvement. Female patients demonstrated greater preservation of hair shaft diameter. No significant differences were observed according to previous COVID-19 infection, and no severe adverse events occurred. Conclusions Standardized A-PRP infiltration provides a safe and effective regenerative approach for AGA, with maintained clinical improvement during long-term follow-up. These findings support the role of standardized delivery protocols in improving reproducibility and therapeutic consistency in regenerative hair restoration.